CONCURRENCE OF EMPIRICAL ANTIBIOTIC THERAPY WITH THE RESULTS OF BACTERIOLOGICAL ANALYSIS IN THE TREATMENT OF ODONTOGENIC PURULENT-NECROTIC PROCESSES OF THE MAXILLOFACIAL REGION - Varzhapetian, A.S.; Sydor, O.V.; Strohonova, T.V.; Buniatian, Kh.А. (World of Medicine and Biology, 2025)
In connection with the constant development of the spectrum of sensitivity of infectious agents, the dynamic development of antimicrobial resistance and the view of modern medicine on rational antibacterial therapy, we consider it appropriate to study the current state of antibacterial resistance of the microbial composition of odontogenic purulent-necrotic foci of the maxillofacial region. The mismatch of microflora sensitivity to the prescribed antibiotic occurred in 66.7 % of cases. Most often, in postoperative surgical wounds due to the opening of purulent-necrotic foci of the maxillofacial region, colonization of Str. mitis, S. pyogenes, S. epidermidis, and also Pseudomonas spp. Antibacterial drugs of the Access group, to which the microbiota of the studied wounds is likely sensitive, were found: clindamycin, ampicillin, gentamicin. The use of clindamycin as a starting antibacterial drug for the treatment of purulent-necrotic lesions of the maxillofacial region may be appropriate not only in cases where the patient is allergic to beta-lactams.
Keywords: treatment; antibiotic therapy; clinical study; clinical cases; inflammation; analysis